2012
DOI: 10.2527/jas.2011-4515
|View full text |Cite
|
Sign up to set email alerts
|

Correlated responses in sow appetite, residual feed intake, body composition, and reproduction after divergent selection for residual feed intake in the growing pig1

Abstract: Residual feed intake (RFI) has been explored as an alternative selection criterion to feed conversion ratio to capture the fraction of feed intake not explained by expected production and maintenance requirements. Selection experiments have found that low RFI in the growing pig is genetically correlated with reduced fatness and feed intake. Selection for feed conversion ratio also reduces sow appetite and fatness, which, together with increased prolificacy, has been seen as a hindrance for sow lifetime perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
64
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 37 publications
11
64
1
2
Order By: Relevance
“…Repeatability estimates were low to high for lactating performance traits and for thermoregulation traits (>0.36) because of strong permanent environmental effect for some traits such as ADFI or RR. The heritability estimate of ADFI (0.26 ± 0.08) was in agreement with estimates obtained in studies performed in temperate conditions such as for commercial crossbred sows reared in the Netherlands (h 2 between 0.19 and 0.27; Bergsma and Hermesch, 2012), or for purebred Large White lines reared in France (h 2 = 0.26 ± 0.07; Gilbert et al, 2012). However, the estimate of heritability of ADFI of our study is greater than the weighted mean of heritability estimates of ADFI (0.08 ± 0.04) obtained in commercial mainstream breeds in the tropics from meta-analysis performed by Akanno et al (2013).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Repeatability estimates were low to high for lactating performance traits and for thermoregulation traits (>0.36) because of strong permanent environmental effect for some traits such as ADFI or RR. The heritability estimate of ADFI (0.26 ± 0.08) was in agreement with estimates obtained in studies performed in temperate conditions such as for commercial crossbred sows reared in the Netherlands (h 2 between 0.19 and 0.27; Bergsma and Hermesch, 2012), or for purebred Large White lines reared in France (h 2 = 0.26 ± 0.07; Gilbert et al, 2012). However, the estimate of heritability of ADFI of our study is greater than the weighted mean of heritability estimates of ADFI (0.08 ± 0.04) obtained in commercial mainstream breeds in the tropics from meta-analysis performed by Akanno et al (2013).…”
Section: Resultssupporting
confidence: 87%
“…The heritability estimate of sow proportion of BW change during lactation (0.20 ± 0.07) was in accordance with the 0.20 heritability estimate of sow BW change score reported in Rydhmer's review (2000) or BW losses (in kilogram) reported by Bergsma et al (2008). These values are slightly lower than the 0.13 ± 0.05 heritability estimate of change of BW of the sow during lactation reported by Gilbert et al (2012).…”
Section: Resultssupporting
confidence: 86%
“…The heritability estimated for LW in the present study (h 2 = 0.22, PSD = 0.05) is comparable to previously published reports about preweaning growth traits in other populations (Högberg and Rydhmer, 2000;Bergsma et al, 2008) and previous estimates from the studied Norwegian Landrace population Lundgren et al, 2012), but higher than the heritability for litter weight at 3 weeks (h 2 = 0.09), recently estimated by Gilbert et al (2012).…”
Section: Heritabilitiessupporting
confidence: 87%
“…The estimated heritabilities for appetite during the first 3 weeks (APP; h 2 = 0.07, PSD = 0.03) and for feed intake at 3 weeks (FEED; h 2 = 0.06, PSD = 0.03) were, however, lower than estimates previously presented in the literature. Bergsma et al (2008) estimated the heritability for voluntary feed intake during the whole lactation period at 0.30, Gilbert et al (2012) at 0.26 and Bergsma et al (2013) at 0.23. Bunter et al (2010) reported a heritability of average lactation feed intake at 0.15, and Hermesch et al (2010) estimated the heritability at 0.10 during early lactation (5 to 14 days).…”
Section: Heritabilitiesmentioning
confidence: 99%
See 1 more Smart Citation